Export performance of tea industry in south India in the context of economic liberalization - Radha Mani A (Department of Rural Banking and Finance Management,College of Co Operation Banking and Management, 2005)
The present study entitled “EXPORT PERFORMANCE OF TEA INDUSTRY IN SOUTH INDIA IN THE CONTEXT OF ECONOMIC LIBERALIZATION” was conducted with the following objectives.